Dayananda Saraswati and the Vedic Canon: Understanding Swami’s Programme of Socio- Cultural Change - Dhanda, Praveen (Journal of Advanced Research in Humanities and Social Sciences, 2023)
This paper seeks to analyse Swami Dayananda Saraswati’s sui generis intellectual practice with reference to the Vedic canon and how this engagement created the ground for his influential project of social reform and socio-cultural change. By primarily drawing from the work of J. T. F. Jordens this essay shows that Dayananda advanced at least three iconoclastic moves concerning the Vedic corpus. First, he restricted the Vedas to the Samhitas proper and heralded that only those subsequent texts or aspects thereof were to be accepted as authentic that were in consonance with the Vedas. Second, the Swami devised a hermeneutic framework for the interpretation of Vedic texts based on logical reasoning and morality on the one hand and rules of grammar on the other. Third, Dayananda himself came up with his translation and interpretation of the Vedas in Hindi, abrogating the age old authority structure of the orthodoxy. These heretic moves of Dayananda, it is suggested, propelled the intellectual life force and supplied the doctrinal precepts of one of the most influential sociopolitical reform movements in modern India. How to cite this article:  Dhanda P. Dayananda Saraswati and the Vedic Canon: Understanding Swami’s Programme of Socio-Cultural Change. J Adv Res Humani Social Sci 2023; 10(1): 8-11. DOI: https://doi.org/10.24321/2349.2872.202302